Effect of Onion Filtrate Concentration (Allium cepa L.) and Soaking Time on the Viability and Vigor of Cabbage Seeds (Brassica oleracea L.) - Faqma Pramesti, Brigita; Sari Kusuma Dewi (LenteraBio : Berkala Ilmiah Biologi, 2025)
Storing seeds for too long has an impact on the low quality of cabbage production. An alternative method to encourage cabbage growth is giving onion filtrate, which contains the growth hormones auxin and gibberellin. This research aims to determine the effect of the combination of onion filtrate (Allium cepa L.) concentration (0%, 50%, 75%, and 100%) and soaking time (0 hour, 3 hours, 6 hours, and 9 hours) on the viability and vigor of cabbage seeds (Brassica oleracea L.). The research design used a Randomized Block Design repeated 3 times, so that 48 research units were obtained. The obtained seed viability and vigor data, namely germination power, vigor index, growth rate, and simultaneity of growth, were analyzed for normality and homogeneity, then tested by Kruskal-Wallis and Mann-Whitney tests if significant. The results showed a significant effect on the treatment of onion filtrate concentration and soaking time on several parameters of seed viability and vigor. The concentration of onion filtrate at 75% affected the vigor index and the simultaneity of cabbage growth. The soaking time of 0 hours affected the germination power and vigor index of expired cabbage (B. oleracea L.) seeds.